Kebutuhan pemakaian gigi tiruan pasca pencabutan gigi - Muhammad Rinaldy; Mourent Miftahullaila; Jumaidah Nasution (Prima Journal of Oral and Dental Sciences, 2019)
The loss of teeth is when a tooth falls out from the socket caused by trauma, caries, and periodontal disease. It can be a big problem when there is no continuous treatment. Knowledge can influence one’s attitude toward using imitation teeth service. The objective of the research was to find out the description of patients’ level of knowledge and attitude toward the need for wearing imitation teeth in the post-tooth extraction in RSGM Prima, Medan, in 2018. The research used descriptive method. The population was 379 adult patients who had their teeth extracted from January until August, 2018 in RSGM Prima, and 80 of them were used as the samples with inclusion criteria. The result of the research showed that 58 respondents (72.5%) had moderate knowledge and 53 respondents (66.2%) had negative attitude. The conclusion was that the patients’ level of knowledge and attitude toward the need for wearing imitation teeth in the post-tooth extraction in RSGM Prima, Medan, in 2018 was bad.